Benzo(a)pyrene Enhanced Dermatophagoides Group 1 (Der f 1)-Induced TGFβ1 Signaling Activation Through the Aryl Hydrocarbon Receptor–RhoA Axis in Asthma - Wang, Eryi; Tu, Wei; Do, Danh C.; Xiao, Xiaojun; Bhatti, Shehar B.; Yang, Liteng; Sun, Xizhuo; Xu, Damo; Yang, Pingchang; Huang, Shau-Ku; Gao, Peisong; Liu, Zhigang (Frontiers in Immunology, 2021)
We have previously demonstrated that benzo(a)pyrene (BaP) co-exposure with dermatophagoides group 1 allergen (Der f 1) can potentiate Der f 1-induced airway inflammation. The underlying mechanism, however, remains undetermined. Here, we investigated the molecular mechanisms underlying the potentiation of BaP exposure on Der f 1-induced airway inflammation in asthma We found that BaP co-exposure potentiated Der f 1-induced TGFβ1 secretion and signaling activation in human bronchial epithelial cells (HBECs) and the airways of asthma mouse model. Moreover, BaP exposure alone or co-exposure with Der f 1 induced aryl hydrocarbon receptor (AhR) activity was determined by using an AhR-DRE (dioxin-responsive element) reporter plasmid. The BaP and Der f 1 co-exposure-induced TGFβ1 expression and signaling activation were attenuated by either AhR antagonist CH223191 or AhR knockdown in HBECs. Furthermore, AhR knockdown led to the reduction of BaP and Der f 1 co-exposure-induced active RhoA. Inhibition of RhoA signaling with fasudil, a RhoA/ROCK inhibitor, suppressed BaP and Der f 1 co-exposure-induced TGFβ1 expression and signaling activation. This was further confirmed in HBECs expressing constitutively active RhoA (RhoA-L63) or dominant-negative RhoA (RhoA-N19). Luciferase reporter assays showed prominently increased promoter activities for the AhR binding sites in the promoter region of RhoA. Inhibition of RhoA suppressed BaP and Der f 1 co-exposure-induced airway hyper-responsiveness, Th2-associated airway inflammation, and TGFβ1 signaling activation in asthma. Our studies reveal a previously unidentified functional axis of AhR-RhoA in regulating TGFβ1 expression and signaling activation, representing a potential therapeutic target for allergic asthma.